Who benefits from share splits? - T. A. Cross; C. Firer (South African Journal of Business Management, 1986)
The objective of this study was to carry out an investigation into the excess return behaviour of companies on the Johannesburg Stock Exchange which split their shares in the period 1972 - 1984. The concept of an event study was used in the analysis. Positive average residuals were observed in the months leading up to the split. In the month of the split large average excess returns were displayed. However, no long-term favourable effects on share price were found. Splits appeared to be a reaction to a sustained period of above-average returns rather than the cause of such returns. The splitting of a company's shares does not appear to influence the share's rand value traded.
Keywords: 650